Buy or Bye? The Implementation of Augumented Reality to Enhance Consumer Willingness to Buy Cosmetics - Furqon, Salsa Angraeni; Alfansi, Lizar (Universitas Mercu Buana, 2025)
This study explores how Augmented Reality (AR) features affect user experience and to what extent they contribute to users' purchase intention for cosmetic products on Shopee. As AR technology becomes increasingly integrated into online retail, key features such as personalization, interactivity, and detailed product information enhance user experience, which may increase consumer willingness to purchase. The aim of this study is to investigate whether using AR on Shopee can positively influence consumers' intention to buy. Employing a quantitative research approach, and the data collection tool use questionnaire by google form. In this study, the sample consist of 205 specifically gen-Z who have interacted with AR features. This study was conducted using SMARTPLS 4.1.0.8 software was used to analyze the data. This study found that the use of AR with information, personalization and interactivity features can improve user experience which explains that the higher the positive experience of AR users, the more it will affect the user's desire to buy cosmetic products.